Effect of Collection Technique on Yield of Bovine Oocytes and the Development Potential of Oocytes from Different Grades of Oocytes - Sianturi, R.G; Thein, M; Wahid, H; Rosnina, Yono C (Indonesian Journal of Animal and Veterinary Sciences, 2002)
Oocyte collection technique is important to obtain a maximum number of oocytes to be employed on in vitro production of embryos. In this study, immature bovine oocytes were collected from slaughterhouse ovaries by two techniques: aspiration of 2- to 6-mm follicles and slicing. Following collection, oocyte qualities were classified into four categories (A, B, C, and D) on the basis of cumulus attachment. Oocytes of each category were matured in vitro in CO2 incubator for 22-24 hours and cumulus expansion and maturation rates were observed. The total number of oocytes (group A+B+C+D) and yield of good quality oocytes (only group A and B) recovered per ovary by aspiration were 12.02 and 8.21, and by slicing were 29.38 and 19.65 (P<0.01), respectively. The total cumulus cells expansion rates of A, B, C and D oocytes were 97.1%, 88.3%, 6.0% and 20.6% respectively. Maturation rates for A, B and C categories of oocytes were 91.4%, 82.3% and 35.0% respectively while no matured oocyte was observed for group D oocytes. Maturation rates were significantly different between group A and C and also between B and C but not between A and B (P<0.05). In conclusion, slicing technique recovered more oocytes per ovary (2.4 times) than that of aspiration and the best maturation rate was observed from category A oocytes which surrounded by more than 3 layers of cumulus cells. However oocytes of category A and B can be considered as good quality oocytes. Â  Key words: Collection technique, aspiration, slicing, oocyte quality, maturation